Managerial efficiency in public sector : patterns and problems in Nigeria - Balogun, M.J. (Ile Ife, Nigeria : University press, Ile Ife, 1980)
This book is a compilation of presentations at a symposium on productivity and efficiency in the public service organized by the department of management and accounting, university of Ile Ife, Nigeria
Includes bibliographical references.
ijb 26/09/2018
Loans
Keywords: Mangerial economics; Mangerial economics--Public sector